Disclosure of intellectual capital information, firm value and intangible assets value: a study on top 50 brand companies in Malaysia - Inaliah Mohd Ali (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2010)
FRS 138 specifically provides that internally generated goodwill, brands, mastheads, publishing titles, customer lists and items similar in substance should not be recognized as assets. Therefore, brands are not recognized by the companies because they are internally developed. However, external consultants do assess and evaluate the brand value of companies in UK, Australia, Singapore and including Malaysia. The external consultant is able to derive at some reliable measure to obtain the brand values of companies in some countries. This study aims to find whether brands are value relevant to the users. The total identifiable capitalised intangible asset is also found to be related to the firm value. This study reports the results that in addition to traditional measures, brands also adds value to the users and stakeholders in their decision making process. Further, this study seeks to measure the intellectual capital performance of the top 50 brand companies in Malaysia. The findings allowed the companies to acknowledge their efficiency ranking, to establish priorities in developing their strategic management plans which in turn will affect their future performance.